Metal–Organic‐Framework‐Derived Carbon Nanostructures for Site‐Specific Dual‐Modality Photothermal/Photodynamic Thrombus Therapy - Fengrong Zhang; Yuehong Liu; Jiani Lei; Shunhao Wang; Xunming Ji; Huiyu Liu; Qi Yang (Advanced Science, 2019)
Abstract Although near‐infrared (NIR)‐light‐mediated photothermal thrombolysis has been investigated to overcome the bleeding risk of clinical clot‐busting agents, the secondary embolism of post‐phototherapy fragments (>10 µm) for small vessels should not be ignored in this process. In this study, dual‐modality photothermal/photodynamic thrombolysis is explored using targeting nanoagents with an emphasis on improving biosafety as well as ameliorating the thrombolytic effect. The nanoagents can actively target glycoprotein IIb/IIIa receptors on thrombus to initiate site‐specific thrombolysis by hyperthermia and reactive oxygen species under NIR laser irradiation. In comparison to single photothermal thrombolysis, an 87.9% higher re‐establishment rate of dual‐modality photothermal/photodynamic thrombolysis by one‐time treatment is achieved in a lower limb thrombosis model. The dual‐modality thrombolysis can also avoid re‐embolization after breaking fibrin into tiny fragments. All the results show that this strategy is a safe and validated protocol for thrombolysis, which fits the clinical translational trend of nanomedicine.